2017
DOI: 10.1016/j.fertnstert.2017.07.028
|View full text |Cite
|
Sign up to set email alerts
|

Infertility & mortality

Abstract: OBJECTIVE: Epidemiologic studies have suggested that nulligravid women have a shorter life span than their parous counterparts. The effect of infertility, as opposed to elective nulligravidity, on mortality is unclear. Our objective was to determine the association of a history of infertility with all-cause mortality.DESIGN: Retrospective cohort study MATERIALS AND METHODS: This study included women (age 55-74) who were prospectively enrolled in the Prostate Lung, Colorectal, and Ovarian (PLCO) Cancer screenin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…A recently presented large retrospective study at the American Society for Reproductive Medicine Scientific Congress including more than 78,000 women demonstrated that women with infertility have higher all-cause mortality compared to fertile women ( 133 ). Interestingly, diabetes was identified as a main primary cause of mortality, although similar diabetes prevalence in both groups was found.…”
Section: Reproduction/sex Hormones-related High-risk Groups and Intermentioning
confidence: 99%
“…A recently presented large retrospective study at the American Society for Reproductive Medicine Scientific Congress including more than 78,000 women demonstrated that women with infertility have higher all-cause mortality compared to fertile women ( 133 ). Interestingly, diabetes was identified as a main primary cause of mortality, although similar diabetes prevalence in both groups was found.…”
Section: Reproduction/sex Hormones-related High-risk Groups and Intermentioning
confidence: 99%
“…Millions of couples worldwide have experienced infertility leading to social segregation, with the female being considered the main culprit (Stentz et al, 2019). The inability to conceive after 1 year of regular unprotected sexual intercourse is regarded as infertility (Vander Borght & Wyns, 2018).…”
Section: Introductionmentioning
confidence: 99%